Components of International Finance and Its Impact on Economic Growth in Jordan (1979-2015) - Alkousini, Eyad; Shawaqfeh, Walid (Jordan Journal of Economic Sciences, 2020)
The objective of this study is to measure the impact of the components of international finance (foreign direct investment, external loans and foreign aid) on economic growth in Jordan during the period 1979-2015. For this purpose, time series analysis (cointegration tests and vector error correction model) is used. The stationarity tests found that all the series representing the variables are stable at the first difference. The results also show that there are two cointegration vectors relating the variables. Therefore, the model was estimated using vector error correction model, which showed a long-term relationship between economic growth and explanatory variables. The estimates showed that there is a significant positive effect for both foreign direct investment and foreign aid and insignificant negative effect for external loans. The study concluded number of recommendations, summarized in the need to direct international financing components towards infrastructure and capital projects that deepen the capital role and raise its productivity, and supporting the absorptive capacity (knowledge, skills and experience) of the workforce, by raising the proportion of foreign aid and external loans directed to education, therefore enhancing its role in economic growth in the short and long terms.